Paralipomena of a Pandemic - Roberto Marchesini (Interlitteraria, 2022)
The pandemic, which has affected the whole world and has many victims, changing our lifestyle and having its own narrative structure that would be interesting to retrace. Undoubtedly, despite science fiction getting us used to dystopian and apocalyptic scenarios, the sudden epidemiological emergency caught us unprepared. We could hardly have thought of suddenly giving up habits that we considered consolidated, such as being able to travel, meet friends, gather in public places, go to a restaurant, go to school. The pandemic suddenly cancelled all of this. But what caused this pandemic? Perhaps a simple virus from an Asian wet market? Perhaps the extreme connectivity of the human network? Perhaps the ecological alterations we have caused? Or is the pandemic the result of a deeper cultural crisis?